2020
DOI: 10.1186/s12885-020-07644-0
|View full text |Cite
|
Sign up to set email alerts
|

Toluidine blue versus frozen section for assessment of mucosal tumor margins in oral squamous cell carcinoma

Abstract: Background When the resected specimen is sent for intraoperative margin assessment, all margins are grossly checked, and selected margins undergo a frozen section (FS) examination. Therefore, there is a possibility of sampling error. This study evaluated the effectiveness of using toluidine blue (TB) as an intraoperative triage screening tool to detect positive mucosal margins of the resected specimens of oral squamous cell carcinoma (OSCC) and serve as a guide for FS sampling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Additionally, the field of view is limited by the probe’s size and its acoustic penetration depth. Most other techniques for in-vivo assessment primarily reveal only the tumor’s mucosal extent ( 9 , 11 , 13 ). As no superior in-vivo technique has emerged thus far, ex-vivo margin assessment remains crucial for margin control.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the field of view is limited by the probe’s size and its acoustic penetration depth. Most other techniques for in-vivo assessment primarily reveal only the tumor’s mucosal extent ( 9 , 11 , 13 ). As no superior in-vivo technique has emerged thus far, ex-vivo margin assessment remains crucial for margin control.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from iodine staining, staining with toluidine blue has also been researched. However, the studies of concern [ 51 , 52 ] stained the resection specimen, but only after the resection was completed. These studies concluded that this stain is highly sensitive to SCC in the resection margins but has a low PPV.…”
Section: Discussionmentioning
confidence: 99%
“…The specimen imaging techniques are agnostic to the fluorescent agent used and may thus also apply beyond paniatumumab-IRDye800CW ( 20), (21) (22). It is worth mentioning that non-fluorescent optical dyes have been investigated for margin analysis with promising results (23,24) (25).…”
Section: Discussionmentioning
confidence: 99%